KEARIFAN LOKAL DALAM SISTEM MANAJEMEN PEMELIHARAAN KERBAU RAWA DI KABUPATEN MUSI RAWAS UTARA - Bagus Dimas Setiawan; Zulhapi Utama Adlan; Sadjadi (Wahana Peternakan, 2022)
The research aims to analyze the potential of swamp buffalo and the form of local wisdom in the management system of maintaining swamp buffalo to support sustainable livestock development. This research is descriptive qualitative. The data used are primary data and secondary data with survey methods through interviews and direct observation. This research was carried out in 2 (two) stages, namely: (1) identification of the development base area with LQ analysis and (2) analyzing local wisdom in the management system of maintaining swamp buffalo. The data obtained were tabulated and displayed in the form of tables and figures and then analyzed descriptively qualitatively. The results showed that the base area for buffalo cattle development was in three sub-districts, namely Ulu Rawas District, Rupit District, and Rawas Ulu District. The management system for keeping buffaloes is maintained ekstensif and local wisdom in the management system for raising swamp buffalo in Musi Rawas Utara Regency is by using a rolling picket system and making cages in groups. This research is expected to be an improvement for the swamp buffalo population as well as the introduction of a management system for maintaining swamp buffalo with local wisdom to support sustainable livestock development. Keywords: Local Wisdom, Maintenance, Swamp Buffalo, North Musi Rawas